2017
DOI: 10.1186/s12885-017-3346-x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risks in a population-based study of 70,570 agricultural workers: results from the Canadian census health and Environment cohort (CanCHEC)

Abstract: BackgroundAgricultural workers may be exposed to potential carcinogens including pesticides, sensitizing agents and solar radiation. Previous studies indicate increased risks of hematopoietic cancers and decreased risks at other sites, possibly due to differences in lifestyle or risk behaviours. We present findings from CanCHEC (Canadian Census Health and Environment Cohort), the largest national population-based cohort of agricultural workers.MethodsStatistics Canada created the cohort using deterministic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 57 publications
4
62
0
11
Order By: Relevance
“…In a previous large Canadian cohort study linked with cancer registry records, hazard ratios of the agriculture sector for lung, colon, bladder, kidney and liver cancers were found to be significantly lower than for other occupational workers . The risk reduction observed for kidney, bladder and colon cancers may be because of the working conditions of agricultural workers that involve high physical activity, a recognized modifiable risk factor for such cancers .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a previous large Canadian cohort study linked with cancer registry records, hazard ratios of the agriculture sector for lung, colon, bladder, kidney and liver cancers were found to be significantly lower than for other occupational workers . The risk reduction observed for kidney, bladder and colon cancers may be because of the working conditions of agricultural workers that involve high physical activity, a recognized modifiable risk factor for such cancers .…”
Section: Discussionmentioning
confidence: 89%
“…Such workers deal with many potential hazards that include pesticides, chemical and biological agents, and the operation of heavy equipment. However, a lower prevalence of smoking plus high occupational activity has been reported for this sector and this may have influenced the low mortality and morbidity rates from cancers observed among farmers …”
Section: Discussionmentioning
confidence: 99%
“…Persistence in the environment, ability to concentrate up the food chain, continued detection in breast milk, and ability to be stored in the adipose tissue of animals and humans are some of the reasons stated. 11,12 More studies need to be done in developing country setting for building evidence regarding this association. No significant association was observed between cancer and source of drinking water supply among residents.…”
Section: Discussionmentioning
confidence: 99%
“…Despite methodological issues in some studies, the exposure to potential or confirmed carcinogens such as herbicides and pesticides commonly used by agricultural workers have been pointed out as key determinants of the cancer risk observed in agricultural populations. Some studies found a different pattern of risk according to sex [86] or even in female spouses of pesticide applicators [87]. Glyphosate is the most commonly used herbicide in the world and recent meta-analysis points out a marginally significant positive association with MM [88].…”
Section: Occupational MMmentioning
confidence: 99%